Deleterious Variation in BR Serine/Threonine Kinase 2 Classified a Subtype of Autism - Deng, Jingxin; Wang, Yi; Hu, Meixin; Lin, Jia; Li, Qiang; Liu, Chunxue; Xu, Xiu (Frontiers in Molecular Neuroscience, 2022)
Recently, deleterious variants in the BR serine/threonine kinase 2 (BRSK2) gene have been reported in patients with autism spectrum disorder (ASD), suggesting that BRSK2 is a new high-confidence ASD risk gene, which presents an opportunity to understand the underlying neuropathological mechanisms of ASD. In this study, we performed clinical and neurobehavioral evaluations of a proband with a de novo nonsense variant in BRSK2 (p.R222X) with other reported BRSK2 mutant patients. To validate BRSK2 as an ASD risk gene, we generated a novel brsk2b-deficient zebrafish line through CRISPR/Cas9 and characterized its morphological and neurobehavioral features as well as performed molecular analysis of neurogenesis-related markers. The proband displayed typical ASD behaviors and language and motor delay, which were similar to other published BRSK2 mutant patients. Morphologically, brsk2b-/- larvae exhibited a higher embryonic mortality and rate of pericardium edema, severe developmental delay, and depigmentation as well as growth retardation in the early developmental stage. Behaviorally, brsk2b-/- zebrafish displayed significantly decreased activity in open field tests and enhanced anxiety levels in light/dark tests and thigmotaxis analysis. Specifically, brsk2b-/- zebrafish showed a prominent reduction of social interaction with peers and disrupted social cohesion among homogeneous groups. Molecularly, the mRNA expression levels of homer1b (a postsynaptic density scaffolding protein), and mbpa, mpz, and plp1b (molecular markers of oligodendrocytes and myelination) were increased in the brain tissues of adult brsk2b-/- zebrafish, while the expression level of isl1a, a marker of motor neurons, was decreased. Taken together, for the first time, we established a novel brsk2b-deficient zebrafish model that showed prominent ASD-like behaviors. In addition, the disturbed mRNA expression levels of neurogenesis-related markers implied that the processes of postsynaptic signaling as well as oligodendrocytes and myelination may be involved. This discovery may suggest a path for further research to identify the underlying neuropathological mechanisms between BRSK2 and ASD.